Women psychiatrists in Iraq: breaking barriers in career development - Noor Ali Hasan; Maha Sulaiman Younis; AbdulRahman A. Saied (Middle East Current Psychiatry)
Abstract Iraqi psychiatrists pioneered the commencement of mental health services eight decades ago and became the cornerstone of its development over the years despite the profound challenges of wars, conflicts, shortages of resources, and social stigma towards psychiatry in general. The purpose of this paper is to highlight the contributions that women make to mental health services, even though they are underrepresented in positions of leadership in psychiatry. We conducted a comprehensive review of existing literature and the archives of educational psychiatric institutes, personal communication with the psychiatrists in charge, and scrutinized the search engines for the latest data. Pathways to academia were identified as limited by financial support, engagement and coordination between academia and clinical services, and flexible working. The total number of psychiatrists has increased recently, with the remarkable contribution of younger women psychiatrists who provide psychiatric care and aspire to better professional productivity. Iraq can create a more effective and inclusive mental health treatment system by tackling structural, budgetary, and cultural obstacles. The contribution of female psychiatrists must be recognized and supported as the need for mental health services becomes increasingly critical.